Application of building information modelling for reinforcement waste minimisation. Issue 1 (6th February 2018) - Chidambaram, Saminathan
Abstract : The primary objective of this paper is to explain how successful implementation of BIM can contribute to the reduction of waste in the construction projects. Traditional construction processes include highly wasteful activities due to lack of automation and innovation. True BIM is one that holds all data in one place. This paper also discusses about how reinforcement information can be efficiently managed through BIM to maximise coordination between project parties and using 3D digital models at site for fabrication and construction. The digital reinforcement modelling process is gaining momentum due to a great number of value additions to achieve potential savings in all stages of project including designing, modelling, optimising, fabricating and steel placing. This paper also focuses on collaboration, such as integrated project delivery to streamline the project processes and workflows to achieve greater efficiency, and de-risking the construction processes. The next challenges are to optimize the reinforcement sizes and lengths for reducing reinforcement scraps. These BIM approaches can reduce, reuse, recycle, and manage the wastes generated during construction through a robust clash resolution process, data rich modelling, detailing, and prefabrication strategies. The key benefits of BIM are to ensure 100% buildability through synchronised design and site layout. It aims to provide cost effective solutions through modern approaches such as value engineering and early contractor involvement. The digital fabrication process can be used to automate the reinforcement fabrication process by establishing a link between the fabrication system and BIM models.